Legal Study on the Payment Mechanism of Copyright Royalties and Its Implications in the Indonesian Creative Industry - Ibrahim; Fakrulloh, Zudan Arief (Greenation Publisher & Yayasan Global Resarch National, 2025)
The rapid development of the creative industry in Indonesia has prompted the emergence of various debates regarding the mechanism for payment of copyright royalties, especially related to direct and indirect payments to the owners of works. This problem is further complicated by various interpretations of applicable legal provisions, such as those stipulated in Law Number 28 of 2014 Article 2 and Article 3, as well as other implementing regulations that regulate the royalty distributive mechanism. This research aims to criticize and analyze in depth the differences in the royalty payment mechanism, identify existing legal loopholes, and provide recommendations for regulatory adjustments to create a fairer and more transparent system between creators and users of works. This study method uses a normative approach with juridical and comparative analysis, which is complemented by literature review, legal document studies, and case analysis related to the implementation of royalty payments in the creative industry sector. The results show that direct royalty payment mechanisms offer higher revenue transparency and accuracy in financial distribution, while indirect payment systems often lead to less effective administrative complexity and supervision. The analysis also revealed that there are shortcomings in the synchronization of implementation between laws and regulations and industry practices, thus causing potential legal disputes. Overall, this study concludes that regulatory harmonization through revision and sharpening of legal provisions, as well as improving supervisory mechanisms, is a strategic step to overcome copyright royalty polemics, encourage distributive justice, and support the sustainable growth of the creative industry in Indonesia.